Production and decay of charmed mesions in e+e- annihilation at Mathematical expression - Braunschweig, W; Gerhards, R; Kirschfink, F; Martyn, H; Fischer, H; Hartmann, H; Hartmann, J; Hilger, E; Jocksch, A; Wedemeyer, R; Foster, B; Martin, A; et al. (Springer-Verlag, 1989)
We report on a study of inclusive production of D*± mesons in e+e- annihilation at c.m. energies between 28 and 46.8 GeV using the TASSO detector at the PETRA storage ring. A hard D*± energy spectrum is measured with a maximum near ED*±≃0.6 Ebeam. The measured cross section ratio Mathematical expression indicates that D* production accounts for a large fraction of the observed charm production. Two complementary methods have been used to determine the forward-backward asymmetry of charm pair production due to electroweak interference. Combining both measurements the product of the axial vector couplings of the electron and the charm quark to the weak neutral current was determined to be gAegAc=-(0.276±0.073), in agreement with the standard model prediction of -0.25. Using a sample of reconstructed D*± mesons, the relative strength of the strong interaction coupling of the c quark compared to that of an average of all flavours is measured as αs(c)/αs(all)=0.91±0.38±0.15, consistent with the coupling constant being flavour independent. An update of our D0 lifetime measurement is presented, based on a considerable increase in statistics, the final result being Mathematical expression. © 1989 Springer-Verlag.